ทางเลือกในการปรับปรุงเปลือกอาคารเพื่อลดการใช้พลังงาน สาหรับการปรับอากาศในอาคารภาควิชาวิศวกรรมโยธา มหาวิทยาลัยเชียงใหม่ - จิรทัศน์ ประกรณ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this independent study was to create an appropriate approach in order to improve the comfort conditions, with minimum energy consumption for air conditioning, inside the classrooms and offices in the structural engineering building and the hydraulic engineering building at the faculty of engineering, Chiang Mai University. In the study, both buildings were modeled by program Building Energy Code (BEC) to calculate the values of Overall Thermal Transfer Value (OTTV) and the values of Roof Thermal Transfer Value (RTTV) in order to find how to improve those buildings' envelope to meet the concerning regulations for building design with energy conservation. The model simulation by BEC revealed that with the existing conditions of the building the value of OTTV was 36.15 W/m2 which met the criteria of the ministerial regulation. However, the value of RTTV was as high as 89.61 W/m2 failing to pass the concerning regulation. Therefore, a method of spraying insulation foam underneath the roof of both buildings was tried. Though the RTTV value was satisfied but this approach cost too much. The method of putting a 2-inch thick insulation sheets of fiber glass over the ceiling of the classrooms and offices was then tried. This method satisfied both the RTTV value and the cost.The last step of this independent study was to assess how to manage the air conditioners which most of them were old and not in good condition. The study compared two cases of air conditioner replacement: 1) replacing with normal type; and 2) replacing with inverter type. It was found that the breakeven point were after 19.1 years and 8.6 years for case1 and case2, respectively. In conclusion, the appropriate approach for improving the buildings is installing sheets of 2-inch thick fiber glass insulator and replacing the old air conditioners with the inverter type.